2022
DOI: 10.1093/ofid/ofac372
|View full text |Cite
|
Sign up to set email alerts
|

Model-Predicted Impact of ECG Monitoring Strategies During Bedaquiline Treatment

Abstract: Background The M2 metabolite of bedaquiline causes QT-interval prolongation, making ECG monitoring of patients receiving bedaquiline for drug-resistant tuberculosis necessary. The objective of this study was to determine the relationship between M2 exposure and Fridericia-corrected QT (QTcF)-interval prolongation and to explore suitable ECG monitoring strategies for six-month bedaquiline treatment. Methods Data from the PROBe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Although programmatic identification of a prolonged QTc interval has never been shown to reduce mortality in a general population, developing prospective randomized evidence supporting the superiority of specific ECG monitoring strategies or QTc interval action thresholds is implausible given the rarity of torsade de pointes and the difficulty of establishing causality. 7 Nevertheless, several investigators 10 , 26 , 56 have reasonably suggested ECG monitoring schedules either more targeted or less intensive than current regulatory guidelines. Simple, handheld 6-lead devices could reduce the need to perform 12-lead ECG monitoring in resource-limited settings and extend the reach of QTc assessment when needed, resulting in more patient-centered care.…”
Section: Discussionmentioning
confidence: 99%
“…Although programmatic identification of a prolonged QTc interval has never been shown to reduce mortality in a general population, developing prospective randomized evidence supporting the superiority of specific ECG monitoring strategies or QTc interval action thresholds is implausible given the rarity of torsade de pointes and the difficulty of establishing causality. 7 Nevertheless, several investigators 10 , 26 , 56 have reasonably suggested ECG monitoring schedules either more targeted or less intensive than current regulatory guidelines. Simple, handheld 6-lead devices could reduce the need to perform 12-lead ECG monitoring in resource-limited settings and extend the reach of QTc assessment when needed, resulting in more patient-centered care.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, van Beek et al using PROBeX data, simulated a strategy of ECG monitoring and found that the vast majority of patients that should have interrupted bedaquiline treatment due to a QTcF interval >500 ms had already been identified by week 12 ( 20 ).…”
Section: Discussionmentioning
confidence: 99%